Are there differences in treatment effects between labial and lingual fixed orthodontic appliances? A systematic review and meta-analysis - Fadi Ata-Ali; Teresa Cobo; Felix De Carlos; Juan Cobo; Javier Ata-Ali (BMC, 2017)
Abstract Background An evaluation is made of possible differences in treatment effects between labial and lingual fixed appliances. Methods A comprehensive search was made of the PubMed-Medline, Cochrane Library and LILACS databases, with an additional manual search covering the period up until April 2017. There were no restrictions in terms of year of publication or language. Agreement between the authors was quantified by the Cohen kappa statistic. A random-effect model was applied to calculate weighted mean differences with 95% confidence intervals. Results A total of 249 patients corresponding to four eligible studies were included in the systematic review. Among the six angles and distances entered in the meta-analysis, a tendency was observed in lingual appliances to increase the interincisal angle (95% CI −0.80-8.99; p = 0.101) and reduce the angle between the major axis of upper central incisor and the sellar-nasion plane - though statistical significance was not reached (95% CI −5.75-0.32; p = 0.079). Conclusion The results obtained indicate that treatment with lingual appliances favors incisor tipping by exerting lingual crown torque, but there are no differences in cephalometric values between labial and lingual fixed appliances. Because of the small number of included studies, the results of this meta-analysis should be interpreted with caution. Future research should focus on the generation of a consensus document allowing selection of the type of orthodontic approach not only conditioned to the esthetic requirements of the patient but also considering the characteristics of the malocclusion. On the other hand, standardized international guidelines are lacking; the measurements of angles and distances therefore have to be unified with a view to future investigations.